Improvement of the hydrophilicity of 7, 8-dihydroxyflavone by in situ grafting of PEG-A via RAFT polymerization and the drug efficacy tests. (August 2016) - Chen, Tao; Han, Xiaohua; Peng, Zhi; Li, Aihua; Liu, Jingquan
Graphical abstract: Highlights: Biocompatible poly (PEG-A) was grafted onto 7, 8-DHF via in situ RAFT polymerization. The solubility of DHF/PPEG-A was improved by 78 times compared to the unmodified precursor. Both the cytotoxicity and drug efficacy of the synthesized DHF/PPEG-A just slightly decreased. The drug efficacy of DHF/PPEG-A was regained by the hydrolysis in the presence of the esterase D. Abstract: 7, 8-Dihydroxyflavone (7, 8-DHF) is an effective drug for the treatment of Parkinson's disease. However, its application is heavily limited by its poor water solubility. To improve its hydrophilicity, biocompatible poly (ethylene glycol)acrylate (PEG-A) was grafted onto 7, 8-DHF via in situ reversible addition-fragmentation chain transfer (RAFT) polymerization, forming a kind of a drug/polymer composite, DHF/PPEG-A. It was found that the solubility of DHF/PPEG-A was significantly improved by 78 times compared to the unmodified precursor. Impressively, both the cytotoxicity and the drug efficacy of the synthesized DHF/PPEG-A just slightly decreased compared with the unmodified 7, 8-DHF. Moreover, the drug efficacy of DHF/PPEG-A can be regained by the hydrolysis in the presence of the esterase D due to the decomposition to 7, 8-DHF in body. This dramatical improvement of the water solubility of DHF/PPEG-A and the insignificant compromise of its drug cytotoxicity could envision extensive practical clinical administration of 7, 8-DHF for enhanced drug efficacy.